Increased levels of lagging strand polymerase ? in an adult stem cell lineage affect replication-coupled histone incorporation. - Davis, B.E.M.; Snedeker, J.; Ranjan, R.; Wooten, M.; Barton, S.S.; Blundon, J.; Chen, X. (Science advances, 2025)
Stem cells display asymmetric histone inheritance, while nonstem progenitor cells exhibit symmetric patterns in the Drosophila male germ line. Here, we report that components involved in lagging strand synthesis, DNA polymerases ? and ?, have substantially reduced levels in stem cells compared to progenitor cells, and this promotes local asymmetry of parental histone incorporation at the replication fork. Compromising Pol? genetically induces the local replication-coupled histone incorporation pattern in progenitor cells to resemble that in stem cells, seen by both nuclear localization patterns and chromatin fibers. This is recapitulated using a Pol? inhibitor in a concentration-dependent manner. The local old versus new histone asymmetry is comparable between stem cells and progenitor cells at both S phase and M phase. Together, these results indicate that developmentally programmed expression of key DNA replication components is important to shape stem cell chromatin. Furthermore, manipulating one crucial DNA replication component can induce replication-coupled histone dynamics in nonstem cells to resemble those in stem cells.